Cervical cancer screening: Impact of collection technique on human papillomavirus detection and genotyping - Alisa P. Young; Mutiya Olorunfemi; Leigh Morrison; Scott A. Kelley; Anna Laurie; Anna McEvoy; Jill Schneiderhan; Julie Prussack; Marie Claire O'Dwyer; Pamela Rockwell; Philip Zazove; Jonathan Gabison; et al. (Preventive Medicine Reports)
Background: The Food and Drug Administration (FDA) in the US approved primary human papillomavirus (HPV) testing for speculum-based cervical cancer screening ten years ago and, in May 2024, approved the self-collection technique. Our study defines the kappa agreement between self- and speculum-based collection techniques for 15 types of high-risk HPV. Additionally, we describe the sensitivity and specificity ratios for HPV testing using both collection methods. Methods: Participants recruited in 2020–2022 included 97 colposcopy attendees and 96 routine primary care screening attendees aged 30–65, who agreed to self-sample before their clinically scheduled speculum-based exam. Prevalence-based kappa calculated agreement, sensitivity and specificity ratios calculated accuracy using the cervical intraepithelial neoplasia grade 2 or worse (CIN 2+) threshold. Results: The average ages were 45.9 (SD 10.5) and 46.2 (SD 11.0) years for the colposcopy and primary care attendees, respectively. HPV 16, 68, and 39 were the most common types detected. The lower bound of the 95 % Cl for kappa calculations was above 0.81, indicating almost perfect agreement across all HPV genotypes. The sensitivity and specificity ratios were consistent at 1.0 across both collection methods. The HPV positivity rate was significantly higher among colposcopy attendees at 66 % (64/97), compared to 14 % (13/96) among routine primary care screeners. The study identified 17 women with CIN2 + . Conclusions: Primary HPV screening with self-collection is equivalent to speculum-based collection among people aged 30–65. The findings emphasize the utility of self-collection in identifying high-grade lesions and the consistency of HPV detection across different collection methods.